Regression, Surface Constraints And The Acquisition Of Mid Vowels - Schaefer, Ronald P. (Kansas Working Papers in Linguistics, 1979)
Few studies in the phonological development of child speech have focused on the acquisition of vowels. The present paper will deal with the development of the mid vowel categories of one English speaking child. The realization rules which account for the correspondence among the adult-child vowel categories are shown to be functionally related. Further, the pattern of mid vowel development from Stage I to Stage III suggests that these vowel categories can be described by the term regression.